Effects of ammonia on pentylenetetrazole-induced seizure threshold - (:unkn) unknown (KLUWER ACADEMIC/PLENUM PUBL, 1999)
The effect of chronic perfusion of ammonia on the seizure threshold against pentylenetetrazol was studied. Ammonia plus sodium bicarbonate and saline (0.9%) was continuously administered to two groups of rats respectively. All animals were tested three times for seizure threshold, and were then decapitated and the brains removed for analysis of the amino acids. The results showed that the infusion of ammonia increased the seizure threshold, and this protective effect was accompanied by selective changes in brain glutamate and glutamine. Thus, continuous infusion of ammonia may cause an imbalance between excitatory and inhibitory systems in favor of inhibitory systems. These findings may provide insights into the basic mechanisms of seizures observed in hepatic failure, in other hyperammonemic states, and in epilepsy.
Keywords: epilepsy; ammonia; amino acids; glutamate; pentylenetetrazole; models; hepatic encephalopathy; BRAIN